Black-tailed prairie dogs selectively urinate near rabbit urine: the scent of competition between a rodent and a lagomorph?. Issue 1 (2nd January 2016) - Eads, D.A.; Bowser, J.; Poonamallee, M.; Molina, S.; Neill, J.; White, L.
Abstract : Rodents commonly use urine to communicate with conspecifics and might do so with heterospecifics. We exposed black-tailed prairie dogs ( Cynomys ludovicianus ) to water (a control) and urine from different mammals and then noted whether the prairie dogs urinated near the liquid stimuli. Prairie dogs urinated near water during 15% of trials, compared to 3% of trials with coyote ( Canis latrans ) urine, suggesting they avoided urinating in the presence of a predatory stimulus. Prairie dogs most commonly urinated near urine from herbivores, especially Sylvilagus rabbits (89%, relative to 37% for mule deer, Odocoileus hemionus ). Prairie dogs altered the spatial layout of their urine markings depending on the liquid stimulus, using localized markings near water and mule deer urine, but scattered markings near rabbit urine. These results collectively suggest that urine may function as a communicative resource between prairie dogs and rabbits. Prairie dogs and rabbits often live in close proximity and can compete for food, and prairie dogs are sometimes aggressive toward rabbits. Urine signals might enable each species to avoid agonistic encounters, while helping prairie dogs to reduce competition for food.